Membentuk Keluarga Islami untuk Menghadapi Tantangan Zaman Perspektif Syafiq Riza Hasan Basalamah - Hikmah Widiatun Nisa; Irsan (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
The family is understood as a primary group consisting of two or more people who have a network of interpersonal interactions, blood relations, marital relations, and adoption. One of the important obligations of a family leader from an Islamic point of view is to fortify his family members by forming an Islamic family to avoid disobedience, especially as the era of disobedience has become more and more rampant. The problems that will be discussed in this study are what is the definition of an Islamic family, what are the steps to form an Islamic family to face the challenges of the times, and what are the goals of forming an Islamic family. The problems above will be answered through the perspective of Syafiq Riza Hasan Basalamah, who is one of the Islamic leaders in Indonesia. The purpose of this research is to know the definition of an Islamic family from the perspective of Syafiq Riza Hasan Basalamah, to know and find steps and goals to form an Islamic family to face the challenges of the times from the perspective of Syafiq Riza Hasan Basalamah. This research approach uses a qualitative descriptive approach. The results of this study show that: Syafiq Riza Hasan Basalamah states that the definition of an Islamic family is a family that always serves Allah subhaanahu wata'aala. There are four steps in forming an Islamic family which Syafiq Riza Hasan Basalamah explains in his video. And there are three objectives of forming an Islamic family mentioned by Syafiq Hasan Riza Basalamah in his video.